Increasing drought favors nonnative fishes in a dryland river: evidence from a multispecies demographic model. Issue 4 (2nd April 2019) - Rogosch, Jane S.; Tonkin, Jonathan D.; Lytle, David A.; Merritt, David M.; Reynolds, Lindsay V.; Olden, Julian D.
Abstract: Understanding how novel biological assemblages are structured in relation to dynamic environmental regimes remains a central challenge in ecology. Demographic approaches to modeling species assemblages show promise because they seek to represent fundamental relationships between population dynamics and environmental conditions. In dryland rivers, rapidly changing climate conditions have shifted drought and flooding regimes with implications for fish communities. Our goals were to (1) develop a mechanistic multispecies demographic model that links native and nonnative species with river flow regimes, and (2) evaluate demographic responses in population and community structure to changing flow regimes. Each fish species was represented by a stage‐structured matrix, and species were coupled together into a multispecies framework through density‐dependent relationships in reproduction. Then, community dynamics were simulated through time using annual flow events classified from gaged streamflow data. We parameterized the model with vital rates and flow–response relationships for a community of native and nonnative fishes using literature‐derived values. We applied the simulation model to the Verde River (Arizona, USA), a major tributary within the Colorado River Basin, for the past half century (1964–2017). Model validation revealed a match between model projections and relative abundance trends observed in a long‐term fish monitoring dataset (1994–2008). At the beginning of the validation period (1994), model and survey observations showed that native species comprised approximately 80% of total abundance. Model projections beyond the survey data (2008–2017) predicted a shift from a native dominant to a nonnative dominant assemblage, coinciding with increasing drought frequency. Trade‐offs between native and nonnative species dominance emerged from differences in mortality in response to the changing sequence of major flow events including spring floods, summer high flows, and droughts. In conclusion, the demographic approach presented here provides a flexible modeling framework that is readily applied to other stream systems and species by adjusting or transferring, when appropriate, species vital rates and flow‐event thresholds.